They Are Among Us: Pricing Behavior of Algorithms in the Field - Niklas Fourberg; Katrin Marques Magalhaes; Lukas Wiewiorra (International Telecommunications Society (ITS), 2023)
We analyze pricing patterns and price level effects of algorithms in the market segments for OTC-antiallergics and -painkillers in Germany. Based on a novel hourly dataset which spans over four months and contains over 10 million single observations, we produce the following results. First, price levels are substantially higher for antiallergics compared to the segment of painkillers, which seems to be reflective of a lower price elasticity for antiallergics. Second, we find evidence that this exploitation of demand characteristics is heterogeneous with respect to the pricing technology. Retailers with a more advanced pricing technology establish even higher price premiums for antiallergics than retailers with a less advanced technology. Third, retailers with more advanced pricing technology post lower prices which contradicts previous findings from simulations but are in line with empirical findings if many firms compete in a market. Lastly, our data suggests that pricing algorithms takeweb-traffic of retailers' online-shops as demand side feedback into account when choosing prices. Our results stress the importance of a careful policy approach towards pricing algorithms and highlights new areas of risks when multiple players employ the same pricing technology.
Keywords: C13; D83; L13; L41; 330; Algorithmic pricing; Collusion; Artificial intelligence